Classical Syriac - Hakobyan, Arman Eġiši (Gorgias handbooks, 2019)
"A grammar of Classical Syriac. An introductory course of eight lessons presents the Syriac phonology and script, followed by the basic course of 40 lessons. The book is designed to cover one academic year"--